Ranhill SAJ Sdn Bhd / Afini Roslan - Roslan, Afini (Faculty of Business and Management, 2023)
This Industrial Training Report provides an overview of my internship process throughout these six months and highlights key findings, achievements, and lessons learned during the internship period. My internship was conducted at Ranhill SAJ Sdn Bhd from 1st March 2023 to 15th August 2023. The primary objectives of my internship were to gain practical experience in the real working world, develop professional skills, and to complete my degree study as it is a compulsory subject for this last semester. During my first day internship, I was assigned as a Human Resource trainee at HR department under Mrs., Norazimah Binti Aziz. The primary role was to assist Mrs. Norazimah and learn about HR in these company. The responsibilities included helping Mrs. Norazimah solved employee’s issues regarding the medical card company on how to apply it, act as a middle person between employees and HR at Head Quarter, do a HR visit to observe employee’s welfare and conduct some events. These responsibilities provided an opportunity to gain hands- on experience, apply theoretical knowledge, and contribute to the organization's projects and initiatives. Moreover, this Industrial Training Report consists of my profile, my updated resume, company’s profile, training reflection, company’s SWOT Analysis, recommendations and conclusion. SWOT Analysis will be used to evaluate the company’s competitive position which includes its strengths, weaknesses, opportunities, and threat. Thus, by doing this report we can analyze the company’s biggest strength which is RS A J (Ranhill SAJ) is one and only water treatment company that operates in Johor and this company has expanded globally. Meanwhile, in this report also consist of some recommendation that can help the company to improve the weaknesses which are RSAJ lack of young talent and has spent thousand ringgits to maintain the quality of water.